Some Traits of Meiofauna in the Surf Region of the Southern Mediterranean Sea Coast (Alhamama - Susa) - Hajir Alfurjani; Bushry Sargeewah (AlQalam Journal of Medical and Applied Sciences, 2025)
In the winter of 2022, meiofauna diversity in the near-shore sandy bottom surf region of the Southern Mediterranean Sea was established using two study locations in eastern Libya. The most abundant taxa among the seven floatable meiofauna (extracted from sediment samples by flotation) were Foraminifera and Nematoda. Bivalve, Copepoda, Ostracoda, Nemertea, and Turbellaria were the additional taxa that were available. There were four non-floatable meiofauna taxa found: Ostracoda, Bivalve, Gastropod, and Foraminifera. Possible causes of this low diversity of floatable and non-floatable meiofauna include the region’s high wave activity and the nearby harmful human activities. Differences in neighboring coastal anthropogenic activities may have had a greater influence on the interstitial habitat, but the reasons for the between-site variations in meiofaunal diversity remain unknown. Susa had a higher level of meiofaunal diversity than Alhamama. There is a need for new, useful methods for gathering and classifying the smaller meiofauna.